Niveles inmunitarios contra fiebre aftosa en bovinos del Urabá antioqueño 1978 - 1985 (1989)
This paper discribes the results of the protection status of cattle against Foot-and- Mouth Disease (FMD) found during the 1978 to 1985 period. One of the vaccination cycles was considered for each year, and a statistical representative random sample was calculated for both, young and adult cattle. Animals were bled at day 90 postvaccination and neutralizing antibody titers against FMD types A and 0 were assayed by neutralization test in microtiter plates, using BHK21 cells. The value of 1.5 log was considered to discriminate protected from unprotected cattle. During the analyzed period, in young cattle, the percentages of protection against the virus type A ranged from 25.6 to 64.4%, and against the type 0 from 27.9 to 74.2%. The estimated percentages of protection in adult cattle, ranged from 23.1 to 87.7% against the virus type A and from 42.8 to 88.8% against the type 0. The estimated percentages of protection found in adult cattle were, in most of the years, higher (P < 0.05) than those found in young cattle. In the latter category, the inmune response against the virus type 0 was higher than that against the type A. These differences were statistically significant (P < 0.05) in 1979, 1980, 1981 and 1982. From the above results a satisfactory protection status against FMD was deduced, specially since 1980 which has been reflected in a remarkable reduction of FMD outbreaks in this region. Besides, it was confirmed the efficacy of massive and systematic vaccination procedures, complemented by other actions such as control of cattle movement and severe epidemiologic surveillance.